The Promise and Pitfalls of Gender Mainstreaming - Sainsbury, Diane; Bergqvist, Christina (International Feminist Journal of Politics, 2009)
This article examines gender mainstreaming in Sweden, which is an interesting case because several favorable conditions make its implementation likely. It addresses two main questions: (1) to what extent has gender mainstreaming been implemented and (2) what are the consequences? The article first discusses the pros and cons of gender mainstreaming as reflected in the international feminist debate. It then briefly describes the favorable conditions of the Swedish case and subsequently maps out the introduction of gender mainstreaming since 1994, focusing on the process and its politics. It concludes with a discussion of the Swedish experience in terms of the promise and pitfalls of gender mainstreaming identified in the feminist debate and the implications of the Swedish case for feminist theorizing on gender mainstreaming.
Publisher: Routledge _eprint: https://doi.org/10.1080/14616740902789575
Keywords: Sweden; feminist theory; gender equality policies; gender mainstreaming; gender politics

The Aftermath of Feminism: Gender, Culture and Social Change - McRobbie, Angela (SAGE Publications, 2009)
Congratulations to Dr. McRobbie! This book has been named to the list of books for the 2009 Critics Choice Book Award of the American Educational Studies Association (AESA).These essays show Angela McRobbie reflecting on a range of issues which have political consequence for women, particularly young women, in a context where it is frequently assumed that progress has been made in the last 30 years, and that with gender issues now 'mainstreamed' in cultural and social life, the moment of feminism per se is now passed. McRobbie trenchantly argues that it is precisely on these grounds that invidious forms of gender -re-stabilisation are able to be re-established. Consumer culture, she argues, encroaches on the terrain of so called female freedom, appears supportive of female success only to tie women into new post-feminist neurotic dependencies. These nine essays span a wide range of topics, including - the UK government's 'new sexual contract' to young women, - popular TV makeover programmes, - feminist theories of backlash and the 'undoing' of sexual politics, - feminism in a global frame- the 'illegible rage' underlying contemporary femininities.
Google-Books-ID: jmMREuksN10C
Keywords: Social Science / Essays; Social Science / Feminism & Feminist Theory; Social Science / Sociology / General; Social Science / Women's Studies

Loyalty and Longevity in Audience Listening: Investigating Experiences of Attendance at a Chamber Music Festival - Pitts, Stephanie E.; Spencer, Christopher P. (Music and Letters, 2008)
There is currently much concern among arts organizations and their marketing departments that audiences for classical music are in decline, yet there has been little investigation so far of the experiences of long-term listeners that might yield insights into audience development and retention. This paper presents a case study of the Music in the Round chamber music festival, conducted over a three-year period that included the retirement of the host string quartet, the appointment of a new resident ensemble, and associated changes in audience attitudes and priorities. Questionnaire and interview data revealed the challenges faced by audience members in shifting their loyalty to a new ensemble and reappraising their own listening habits and stamina. The interaction between individual listening and collective membership of an audience is discussed, and the potential considered for understanding classical concert-goers as ‘fans’ or ‘consumers’.

The Experiences of Canadian Women in Popular Music: “even on the worst sick no gas freezing canadian middle of january rockie mountain or halifax breakdown there is nothing better to do for a living” - MacKay, Robbie (Université Queen’s, 2008)
Keywords: Bibliographie; Nettoyer

The Girl Hunt: Urban Nightlife and the Performance of Masculinity as Collective Activity - Grazian, David (Symbolic Interaction, 2007)
The purpose of this article is to document the collective nature of gender performance and sexual pursuit, activities typically associated with individual rather than group behavior. Drawing on narrative accounts, I analyze how young heterosexual male students employ the power of collective rituals of homosociality to perform sexual competence and masculine identity by “girl hunting” in the context of urban nightlife. These rituals are designed to reinforce dominant sexual myths and expectations of masculine behavior, boost confidence in one's performance of masculinity and heterosexual power, and assist in the performance of masculinity in the presence of women. This analysis illustrates how contemporary courtship rituals operate as collective strategies of impression management that men perform not only for women but for other men. In doing so, interaction rituals associated with the girl hunt reproduce structures of inequality within as well as across the socially constructed gender divide between women and men.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1525/si.2007.30.2.221

‘Loaded’: indie guitar rock, canonism, white masculinities - Bannister, Matthew (Popular Music, 2006)
Indie alternative rock in the 1980s is often presented as authentically autonomous, produced in local scenes, uncaptured by ideology, free of commercial pressures, but also of high culture elitism. In claiming that the music is avant-garde, postmodern and subversive, such accounts simplify indie's historical, social and cultural context. Indie did not simply arise organically out of developing postpunk music networks, but was shaped by media, and was not just collective, but also stratified, hierarchical and traditional. Canon (articulated through practices of archivalism and connoisseurship) is a key means of stratification within indie scenes, produced by and serving particular social and cultural needs for dominant social groups (journalists, scenemakers, tastemakers, etc.). These groups and individuals were mainly masculine, and thus gender in indie scenes is an important means for deconstructing the discourse of indie independence. I suggest re-envisioning indie as a history of record collectors, emphasising the importance of rock ‘tradition’, of male rock ‘intellectuals’, second-hand record shops, and of an alternative canon as a form of pedagogy. I also consider such activities as models of rational organisation and points of symbolic identification.
Publisher: Cambridge University Press

The Study of Gender in Culture - Cragin, Becca; Simonds, Wendy (Handbook of the Sociology of Gender, 2006)
Keywords: Critical Dialogue; Cultural Study; Feminist Study; Popular Culture; Soap Opera

Sexism and misogyny in American hip-hop culture - Larsen, Jane Kathrine (2006)
The proliferation of hip-hop culture today is so great that we may speak of a modern-day pop-cultural phenomenon. This phenomenon has found its way from the ghetto areas in the Bronx to white suburbia in the U.S. and Europe over the last thirty years. The specific subject for my study is the overt sexism that is present in this culture. Sexism can take on a variety of forms and expressions, as there are various degrees and definitions of this concept. Hence, my aim is to locate some of these definitions and relate them to hip-hop’s expression. The development from a black sub-culture to an immensely successful genre in music is of great interest to my study, in terms of hip-hop as a pop-cultural and sociological phenomenon. There are also cultural, gender, and racial concerns to be considered in this respect, and my account of these includes an exploration of the time and place for the birth and development of hip-hop. The extent of sexism, and even outright misogyny, in hip-hop today is so pervasive, that protests have started to come from every direction of America’s pop-cultural, feminist, and academic sphere. The sociological and pop-cultural factors that are present in this discussion, is related to the topic of gender roles and relationships in African American culture. In my discussion on the hip-hop industry’s responsibility for distributing these negative depictions of women in hip-hop videos and lyrics, I have included some examples from studies that focus on the racial stereotypes in connection to gangsta-rap. The concept of image and authenticity is important in this respect, and there is a level of deliberate marketing strategies behind the lifestyle-oriented aliases of the rap artists. Since hip-hop and rap music traditionally have been overwhelmingly masculine expressions, it is necessary to take a look at the role of female artists within the hip-hop community. In this respect, I find that women have traditionally been rejected or hindered to participate in hip-hop’s brotherhood. Women in hip-hop have thus either tried to make careers for themselves, or adapt into the mass-marketed and male-defined stereotype that in many ways relate to the sexist images that are currently so pervasive. The sexist attitudes represent a point of view that I believe is derived from popularised representations in the media. These representations tally well with the already existing prejudiced opinions that have been created in terms of race discrimination and patriarchal values. Part of the problem with these representations is the lack of alternative images. If there are no counter-images that will speak against the existing sexist depictions, then there will be no progress in terms of addressing sexism directly. The constructed images of African Americans that the media are chiefly responsible for distributing, are what many non-black citizens believe to be the truth about black people. As long as people do not interact socially across ethnic borders, these representations will continue to circulate. In hip-hop culture, this is still ubiquitous in terms of the stereotyping of race. An interesting, and perhaps surprising aspect to some, is the fact that most of hip-hop’s buying audience is white. The negative stereotyping in hip-hop which was initiated by the gangsta-era, was displayed mainly by African American men who acted as criminal gangsters (hence the name), and who lived up to their role as “bad”, thus confirming the stereotyped conception that many non-blacks had of black people. The badness is then articulated within hip-hop’s boundaries through violence and as a glorification of the “thug life” by the men, whereas for women it is commonly expressed as commodified sexuality. Contemporary hip-hop resembles the minstrel shows of the 19th century in this respect, where working class white men dressed up as plantation slaves.
Accepted: 2013-03-12T11:40:46Z
Keywords: Hip-hop culture; Myriam; Perfoming arts

Bouncers: Violence and Governance in the Night-time Economy - Hobbs, Dick; Hadfield, Philip; Lister, Stuart; Winlow, Simon (Oxford University Press, 2003)
"In recent years, the expansion of night-time leisure has emerged as a key indicator of post-industrial urban prosperity, attracting investment, creating employment and re-generating the built environment. These leisure economies are youth-dominated, focusing upon the sale and consumption of alcohol. Unprecedented numbers of young people now flock to town centres that are crammed with bars, pubs and clubs, and the resulting violent disorder has over-run police resources that remain geared to the drinking patterns and alcohol cultures of previous generations. Post-industrial re-structuring has spawned an increasingly complex mass of night-time leisure options through which numerous licit and illicit commercial opportunities flow. Yet, regardless of the fashionable and romantic notions of many contemporary urban theorists, it is alcohol, mass intoxication and profit rather than 'cultural regeneration,' which lies at the heart of this rapidly expanding dimension of post-industrial urbanism. Private security in the bulky form of bouncers fills the void left by the public police. These men (only 7% are women), whose activities are barely regulated by the State, are dominated by a powerful subculture rooted in routine violence and intimidation. Using ethnography, participant observation and extensive interviews with all the main players, this book charts the emergence of the bouncer as one of the most graphic symbols in the iconography of post-industrial Britain." Argumentaire de l'ouvrage.
Google-Books-ID: fTOC5gcecWYC
Keywords: Law / International

All rock and roll is homosocial: the representation of women in the British rock music press - Davies, Helen (Popular Music, 2001)
The British rock music press prides itself on its liberalism and radicalism, yet the discourses employed in music journalism exclude women from serious discussion both as musicians and as fans. In particular, the notion of credibility, which is of vital importance to the ‘serious’ rock music press, is constructed in such a way that it is almost completely unattainable for women.The most important and influential part of the British music press was until recently its two weekly music papers, Melody Maker (MM) and the New Musical Express (NME), both published by IPC magazines. The NME, launched in 1949, contains reviews, concert information and interviews with performers and describes itself as ‘a unique blend of irreverent journalism and musical expertise’ (www.ipc.co.uk). MM, which started life in 1926 as a paper for jazz musicians, had similar content but a greater emphasis on rock, as opposed to pop, music. It was relaunched in 1999 as a glossy magazine, before ceasing publication or, as IPC put it, merging with the NME, in December 2000.
Publisher: Cambridge University Press